A Continuing Saga: Soybean Rust in the Continental United States, 2004 to 2013. (1st April 2014) - Allen, Tom; Hollier, Clayton; Sikora, Edward
Soybean rust (SBR), caused by the fungus Phakopsora pachyrhizi is a significant disease of soybean (Glycine max) throughout the world. SBR was first described from Japan in 1902 and was later observed in several countries in Asia followed by Australia in 1934. The disease was first reported in Africa in the mid-1990s and subsequently detected in South America in 2001. SBR was first detected in the United States in Hawaii in 1994, but was not detected in the continental U.S. until 2004 in Louisiana. Soybean rust is believed to have been carried to the continental U.S. on Hurricane Ivan. The initial detection of SBR set in motion a chain of events that continues to be one of the largest plant disease monitoring efforts to date. Following the discovery of SBR in the continental U.S., a major collaborative effort to monitor the spread and distribution of the disease was initiated by the U.S. Department of Agriculture, Land-grant universities, agricultural industry personnel, and local, regional and national soybean checkoff boards (a support group within each state as well as a national organization that is supported by small amounts of money collected from every bushel of soybean harvested). In 2005, strategically planted soybean monitoring plots, termed "sentinel plots", were established throughout the U.S. and Canada to serve as an early warning system for SBR. Information on the location of the disease was made available to the public via the SBR – Pest Information Platform for Extension and Education (SBR-PIPE) website. In addition, a password protected restricted website on the SBR-PIPE platform, for uploading SBR observations by county or parish, provided predictive models regarding the spread and development of SBR based on the previously provided disease observations. The sentinel plot system, in conjunction with the SBR-PIPE, allowed farmers to make management decisions based on SBR's location and the potential risk to their crop. As a result of this monitoring effort SBR has been detected in a total of 20 states in the U.S. since 2004, as well as Canada and Mexico. In addition to SBR infecting soybean and several other lesser legumes, kudzu (Pueraria montana var. lobata), serves as the primary overwintering host of the pathogen in the U.S. Kudzu, a perennial vine, has been observed in 26 states and in Ontario, Canada and covers an estimated 2.9 million hectares within the U.S. The major concentration of kudzu occurs in the southern U.S. where some states (e.g., Alabama, Georgia and North Carolina) report every county infested with the invasive weed. Kudzu serves as the primary host for SBR during the winter months in states along the Gulf Coast including Alabama, Florida, Louisiana, Mississippi, and Texas.